Komunikasi Fatis dalam Talk Show Sawako no Asa - Edi Sutrisno (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2019)
This study discusses the form of phatic expression and also phatic communication function analyzed based on the phatic theory by Jakobson. The objective of this study is to find out the variation of Japanese phatic expression and phatic communication function in Sawako no Asa Talk Show. The data this study analyses come from Sawako no Asa Talk Show and the research method used is descriptive qualitative. The speeches in the talk show are analyzed using Jakobson theory of Phatic and Communication Function theory by Jumanto. The result of the study found that the forms of Phatic were based on particles, words, phrases in the form of small talk. Phatic communication were used to maintain or reaffirm communication in the talk show. The researcher hope that this study can give reference to other studies in the future, especially studies regarding Phatic Communication in order to create or maintain social relationships. This study in many ways is still lacking, the researcher hope that there will be further studies towards this subject matter.